Can Antinuclear Antibodies (ANA) be Monoclonal?. (30th September 2021) - Biederman, Laura; Satoskar, Anjali A.; Doraiswamy, Mohankumar; Parikh, Samir; Rovin, Brad; Mussio, Brian; Mikhalina, Galina; Brodsky, Sergey V.
Abstract : Background . Nuclear staining by immunofluorescence in a kidney biopsy is often seen in patients with positive antinuclear antibodies (ANA) in the serum. These ANA are usually polyclonal, but herein we report 9 cases with an unusual finding of monoclonal nuclear staining by immunofluorescence on kidney biopsy. Case Presentation . Nine cases with predominant stain for kappa or lambda light chain were identified by searching the renal pathology laboratory database for the past 10 years. All cases had positive stain for only kappa (six cases) or lambda (three cases) light chain in the nuclei. Eight out of nine cases had positive nuclear IgG stain, and one case had positive nuclear IgA stain. Among cases with positive nuclear IgG staining, six cases were positive for IgG1 subclass, one case was positive for IgG2 subclass, and one case was positive for IgG3 subclass. All patients with positive IgG nuclear stain, who had testing for ANA, had positive ANA. Patients with positive IgG1 subclass did not have monoclonal protein in the serum or urine, but the patient with positive IgG2 subclass and lambda light chain stain in the nuclei had IgG lambda monoclonal gammopathy. Conclusions . We identified a new unique pattern of nuclear stain by immunofluorescence in kidney biopsies that suggests the presence of monoclonal ANA. Workup for underlying monoclonal gammopathy is warranted in such patients.